2022
DOI: 10.3389/fnmol.2022.1007889
|View full text |Cite
|
Sign up to set email alerts
|

The role of astrocytes in neuropathic pain

Abstract: Neuropathic pain, whose symptoms are characterized by spontaneous and irritation-induced painful sensations, is a condition that poses a global burden. Numerous neurotransmitters and other chemicals play a role in the emergence and maintenance of neuropathic pain, which is strongly correlated with common clinical challenges, such as chronic pain and depression. However, the mechanism underlying its occurrence and development has not yet been fully elucidated, thus rendering the use of traditional painkillers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 154 publications
0
7
0
Order By: Relevance
“…They communicate with neuronal pre- and postsynaptic terminals and facilitate the modulation of synaptic transmission by releasing neurotransmitters such as glutamate, D-serine and ATP. [ 18 , 27 ] To illustrate, in vitro investigations involving primary hippocampal neurons have revealed that TNF signaling mechanisms regulate synaptic scaling by enhancing the trafficking of glutamate receptors and reducing the abundance of surface GABA receptors. [ 28 ] Neuroimaging inquiries have consistently reported diminished volumes in the prefrontal cortex and hippocampus among patients diagnosed with major depression.…”
Section: Depression and Central Nervous Inflammationmentioning
confidence: 99%
“…They communicate with neuronal pre- and postsynaptic terminals and facilitate the modulation of synaptic transmission by releasing neurotransmitters such as glutamate, D-serine and ATP. [ 18 , 27 ] To illustrate, in vitro investigations involving primary hippocampal neurons have revealed that TNF signaling mechanisms regulate synaptic scaling by enhancing the trafficking of glutamate receptors and reducing the abundance of surface GABA receptors. [ 28 ] Neuroimaging inquiries have consistently reported diminished volumes in the prefrontal cortex and hippocampus among patients diagnosed with major depression.…”
Section: Depression and Central Nervous Inflammationmentioning
confidence: 99%
“…94 The activation of astrocytes is thought to occur after microglial activation, but it has a longer duration and therefore plays a crucial role in the persistence of chronic pain. 94,129 Manipulation of astrocyte activity through optogenetic or chemogenetic methods can effectively regulate chronic pain.…”
Section: Glial Cellsmentioning
confidence: 99%
“…Recent evidence suggests that pain mechanisms cannot be explained solely by neural factors, but alterations of the neuroimmune system, a key player in maintaining homeostasis in the central nervous system (CNS), have been linked to pain induction and maintenance ( Grace et al, 2014 ; Ji et al, 2018 ; Ji et al, 2019 ; Donnelly et al, 2020 ). Astrocytes represent the majority of the glial cells in the CNS and serve critical physiological functions related to neuronal metabolism and synapse processes, but their contribution to the pathophysiology of pain in different brain areas is not clear ( Grace et al, 2014 ; Ji et al, 2014 ; Ji et al, 2016 ; Donnelly et al, 2020 ; Cheng et al, 2022 ). In pathological conditions, astrocytes become activated (“reactive”), undergoing a series of structural and functional changes that serve to protect the brain ( Tian et al, 2012 ; Ji et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In pathological conditions, astrocytes become activated (“reactive”), undergoing a series of structural and functional changes that serve to protect the brain ( Tian et al, 2012 ; Ji et al, 2019 ). A large body of evidence has focused on the contribution of reactive glia to nociceptive processing at the peripheral and spinal cord levels ( Li et al, 2019 ; Miranpuri et al, 2021 ; Xu et al, 2021 ; Cheng et al, 2022 ; Lu and Gao, 2023 ). Astrocyte activation has also been implicated in several brain regions involved in pain processing ( Raghavendra et al, 2004 ; Narita et al, 2006 ; Roberts et al, 2009 ; Chen et al, 2012 ; Kim et al, 2016 ; Ni et al, 2019 ), but the astrocytic contribution to amygdala-related neuroplasticity and behaviors in the context of pain has not been reported.…”
Section: Introductionmentioning
confidence: 99%